This emotional life - Gilbert, Daniel Todd.; Sweet, Jesse; Gazit, Chana; Youngelson, Jack.; WGBH (Television station : Boston, Mass.). Science Unit.; Vulcan Productions; Public Broadcasting Service (U.S.) (Alexandria, VA : [Distributed by] PBS, 2009)
This program explores ways to improve our social relationships, cope with emotional issues, and become more positive, resilient individuals in these difficult times.
disc 1. Family, friends, & lovers (114 min.) -- disc 2. Facing our fears (114 min.) -- disc 3. Rethinking happiness (114 min.).
Title from container.
Originally broadcast as a 3 part television series January 4-6, 2010 on PBS.
Additional resources: Importance of early attachment ; how to build enduring relationships ; stress depression ; post traumatic stress discorder (PTSD) ; grief ; resilience ; finding happiness.
Writers, Daniel Gilbert, Jesse Sweet, Chana Gazit, and Jack Youngelson ; directors, Chana Gazit and Jack Youngelson, original music by Michael Bacon.
Host, Daniel Gilbert.
Rating: TV-PG.
Keywords: Emotions; Mental Health; Interpersonal Relations; Happiness